Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/micr.22495
|View full text |Cite
|
Sign up to set email alerts
|

Donor site morbidity following DIEP flap for breast reconstruction in Asian patients: Is it different?

Abstract: DIEP flap breast reconstruction performed in Asian patients showed acceptable donor-site morbidity without significant complications. This study suggests that donor-site morbidity from harvesting a DIEP flap is comparable to that described in Western literatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
(101 reference statements)
1
26
1
Order By: Relevance
“…Previous studies have shown that patient comorbidities such as smoking, radiated-recipient vessel, and diabetes are significant risk factors for postoperative complications. 8,12,13 Our study demonstrates that it is possible to maximize resident operative experience without compromising patient safety in advanced, complex surgical cases. The factors that lead to these results include the availability of microsurgical education material, animal labs for skills improvement, large microsurgical clinical volume, availability and dedication of the faculty to teaching, and commitment to assuring resident independence at each level of training with appropriate supervision.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that patient comorbidities such as smoking, radiated-recipient vessel, and diabetes are significant risk factors for postoperative complications. 8,12,13 Our study demonstrates that it is possible to maximize resident operative experience without compromising patient safety in advanced, complex surgical cases. The factors that lead to these results include the availability of microsurgical education material, animal labs for skills improvement, large microsurgical clinical volume, availability and dedication of the faculty to teaching, and commitment to assuring resident independence at each level of training with appropriate supervision.…”
Section: Discussionmentioning
confidence: 73%
“…Korean women are generally considered to be thinner than women in other populations, and consequently have a small abdomen [ 9 ]. The mean BMI of the patients in our study was 23.55 kg/m 2 , which may be considered unusual from the standpoint of Western physicians who might think that Koreans are not good candidates for breast reconstruction with an abdominal flap [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the incidence of abdominal complications after autologous reconstruction was ranged from 3.4 to 25.8%. Some reports considered that a higher BMI was associated with higher morbidity in abdominal complications [ 5 7 , 11 ]. However, the bulging and herniation of the donor site is rare in previous reports.…”
Section: Discussionmentioning
confidence: 99%